Healing developmental trauma : how early trauma affects self-regulation, self-image, and the capacity for relationship - Heller, Laurence, 1944-; LaPierre, Aline, 1944- (Berkeley, Calif. : North Atlantic Books, 2012)
"Written for those working to heal developmental trauma and seeking new tools for self-awareness and growth, this book focuses on conflicts surrounding the capacity for connection and introduces the NeuroAffective Relational Model, a unified approach to developmental, attachment, and shock trauma"--Provided by publisher.
Includes index.
Keywords: Neuropsychology; Traumatic shock -- Treatment; Psychic trauma -- Treatment